2021
DOI: 10.1186/s13358-021-00229-9
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of nautilid soft parts inside and outside the conch interpreted as central nervous system, eyes, and renal concrements from the Lebanese Cenomanian

Abstract: Nautilid, coleoid and ammonite cephalopods preserving jaws and soft tissue remains are moderately common in the extremely fossiliferous Konservat-Lagerstätte of the Hadjoula, Haqel and Sahel Aalma region, Lebanon. We assume that hundreds of cephalopod fossils from this region with soft-tissues lie in collections worldwide. Here, we describe two specimens of Syrionautilus libanoticus (Cymatoceratidae, Nautilida, Cephalopoda) from the Cenomanian of Hadjoula. Both specimens preserve soft parts, but only one shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Numerous examples are found in ammonoids dating back to the Devonian (Tanabe et al, 2015a;Klug et al, 2016). They are rarer in the Nautilida, but a few specimens are usable for shape analysis (Klug et al, 2021a). In Coleoids, beaks are found from the end of the Lower Jurassic (Nixon, 2015;Klug et al, 2021b).…”
Section: Palaeontology: Fossil Beaksmentioning
confidence: 99%
“…Numerous examples are found in ammonoids dating back to the Devonian (Tanabe et al, 2015a;Klug et al, 2016). They are rarer in the Nautilida, but a few specimens are usable for shape analysis (Klug et al, 2021a). In Coleoids, beaks are found from the end of the Lower Jurassic (Nixon, 2015;Klug et al, 2021b).…”
Section: Palaeontology: Fossil Beaksmentioning
confidence: 99%
“…The fossil record of soft tissues is best known among octobrachians (e.g., Clements et al, 2017 ; Fuchs et al, 2010 ; Fuchs, 2006a , 2006b ; Klinghardt, 1932 ; Klug et al, 2015 ; Naef 1922 ; Rowe et al, 2022 , 2023 ). Less is known about the soft tissues of decabrachians (Fuchs et al, 2010 ; Fuchs, 2006a , 2006b ; Klug et al, 2016 , 2019 ), and less still about externally shelled (ectocochleate) cephalopods such as ammonoids and nautiloids (De Baets et al, 2013 ; Klug & Lehmann, 2015 ; Klug et al, 2012 , 2015 , 2021a , 2021c ). Some of these reports (Fuchs et al, 2010 , 2021 ; Fuchs, 2006a , 2b ; Klug et al, 2016 , 2020 ; Kruta et al, 2016 ; Rowe et al, 2022 , 2023 ) demonstrated the increased preservational potential for soft tissue anatomy in the coleoid arm crown, which are typically less common than the sclerotized elements such as arm hooks or sucker rings.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to many other soft-tissue details, descriptions of the nervous system of cephalopods have only occasionally found their way into the scientific literature (Fuchs & Larson, 2011a , 2011b ; Fuchs, 2006a , 2006b ; Jattiot et al, 2015 ; Klug et al, 2016 , 2019 , 2021a ; Larson et al, 2010 ), mostly showing parts of the cephalic cartilage. Fossilized axial nerve cords that probably included the intrabrachial ganglia, the brain-like concentrations of neuronal tissues in the arms, have been documented only a few times (Kruta et al, 2016 ; Rowe et al, 2022 , 2023 ) and once unknowingly (Klug et al, 2016 , supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Fossilisation of mollusc soft parts is rare. Soft tissue-preservation is reasonably common in cephalopods (e.g., Kear et al, 1995 ; Klug et al, 2021 a; Klug et al, 2021 b; Hoffmann et al, 2021 ), it is very rare in gastropods (Sutton et al, 2006 ) and quite rare in bivalves (a list of references is given in Table 1 ).…”
Section: Introductionmentioning
confidence: 99%